African Forms of Socialism: A Revolution in Gender? A Historiographical Essay - (:unkn) unknown (My University, 2023)
Like other forms of socialism in the world, African socialisms have often placed strong emphasis on gender equality as part of their revolutionary agenda. While African socialisms are increasingly studied, scholarship on their commitment to gender equality remains scarce. This paper offers a historiographical assessment of this scholarship, comparing the fifteen or so African states that proclaimed themselves to be socialist, either for a few years or for a longer period, during the 1960s, 1970s and 1980s. It highlights the main lines of discourse on women in African socialist regimes, as well as women’s actions and demands within them, and the policies implemented and their effects on women. This assessment opens up new pathways for research on the contradictions in gender dynamics in post-colonial Africa.
Keywords: African Research